2017
DOI: 10.1016/j.schres.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The course of cognitive functioning after first-episode of psychosis: A six month follow-up study

Abstract: Our aim with the present study was to evaluate rank-order and mean-level cognitive functioning stability among first-episode psychosis (FEP) patients, measured using the Cambridge Neuropsychological Test Automated Battery (CANTAB), over a six month period. We also aimed to examine longitudinal measurement invariance and identify factors-such as age, gender, educational level, treatment and psychopathological change scores-potentially linked to cognitive change among patients. In addition, correlations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Thus, although the recent-onset patients demonstrate visuospatial associative memory impairments, these appear to be milder than those observed in chronic patients. Although previous studies have also identified visuospatial associative memory deficits in individuals with chronic schizophrenia (Wood et al ., 2002; Stip et al ., 2005; Donohoe et al ., 2008), prior studies of recent-onset patients found preserved functioning in this domain (Wood et al ., 2002; Barnett et al ., 2005; Wannan et al ., 2018), with deterioration occurring only after illness onset (Haring et al ., 2017; Wannan et al ., 2018). One potential explanation for the visuospatial associative memory deficit in our recent-onset group is their longer duration of illness compared with previous studies (Wood et al ., 2002; Wannan et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although the recent-onset patients demonstrate visuospatial associative memory impairments, these appear to be milder than those observed in chronic patients. Although previous studies have also identified visuospatial associative memory deficits in individuals with chronic schizophrenia (Wood et al ., 2002; Stip et al ., 2005; Donohoe et al ., 2008), prior studies of recent-onset patients found preserved functioning in this domain (Wood et al ., 2002; Barnett et al ., 2005; Wannan et al ., 2018), with deterioration occurring only after illness onset (Haring et al ., 2017; Wannan et al ., 2018). One potential explanation for the visuospatial associative memory deficit in our recent-onset group is their longer duration of illness compared with previous studies (Wood et al ., 2002; Wannan et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Memory impairments are considered to be a core cognitive dysfunction in schizophrenia, with patients exhibiting deficits across a wide range of memory tasks relative to healthy controls. While it has previously been suggested that memory ability is stably impaired in individuals with schizophrenia (Bora and Murray, 2013), recent longitudinal evidence indicates that one particular type of memory, visuospatial associative memory, is preserved in individuals with first-episode psychosis, with deterioration occurring only as the illness progresses (Haring et al ., 2017; Wannan et al ., 2018). It is, therefore, possible that deficits in visuospatial associative memory observed in chronic patients (Wood et al ., 2002; Stip et al ., 2005; Donohoe et al ., 2008) are related to stage-specific brain abnormalities in regions associated with this ability (Bartholomeusz et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%